Diálogos entre Brasil y Colombia: resultados de investigaciones en educación (2020)
The book brings together research papers that analyze important education issues, involving experiences developed in two great nations of the Latin American continent: Brazil and Colombia. Although speaking and writing in different languages, the researchers who participate in the authorship of the texts, analyzing specific realities of their countries, dialogue with each other intensely. The works are the result of academic theses received in the Latin American Doctorate in Education (DLA): "Public Policies and the Teaching Profession", instituted in 2010, and which are also part of the Graduate Program in Education: "Knowledge and Social Inclusion" of the Faculty of Education of the Federal University of Minas Gerais, established in 1971. In accordance with the research lines of the program, the texts of this work deal with different approaches and ways of investigating in education and are organized into three chapters: “Looks to education since decoloniality ”,“ Inclusive education and school coexistence: daily challenges ”,“ Between bars and schools: sociocultural settings to teach-learn ”. In its entirety, the work symbolizes, through the circulation of words, in different languages, with different authors and expressing thematic diversity, a commemoration of the ten years of existence of the Latin American Doctorate in Education. The DLA is consolidated as an instance created to guarantee studies that produce knowledge, having education in Latin America as the central axis of its doctoral research; the focus of this work are the theses that dealt with Colombia or Brazil as opposed to Colombia. In the words of Professor Luiz Alberto de Oliveira Gonçalves, who is the author of the preface: “We hope that each reader can experience, in reading each of the articles gathered in this work, the sensation of being in dialogue with each author or author who dedicated herself to writing these texts for our reflection. Feel at ease ”.